2004
DOI: 10.1111/j.1469-8137.2004.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate translocation determines the phenolic content of Populus foliage: a test of the sink–source model of plant defense

Abstract: Summary• Here, we examine the influence of source-to-sink carbohydrate (CHO) flow on the development of constitutive and inducible levels of phenylpropenoids in hybrid poplar ( Populus nigra × P. deltoides ) foliage to determine if secondary metabolic processes in plant modules can be inhibited in a predictable manner by events such as herbivory and the development of new leaves and reproductive structures, which alter the path of phloem-borne resources.• Phenylpropenoid concentrations were determined for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
112
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 32 publications
11
112
0
1
Order By: Relevance
“…lesions damage vascular tissues in seagrass blades, disrupting the flow of carbohydrates within seagrass blades and resulting in accumulations of phenolics wherever carbohydrates are in overabundance, as predicted by Jones & Hartley (1999). Such responses are known from terrestrial plants, including birch, pine and poplar, and are predicted by the sink/source model of plant defense (Haukioja 1990, Tuomi et al 1991, Honkanen et al 1999, Arnold et al 2004). This model predicts that 'induced' responses arise when the allocation of carbon resources among tissues acting as carbohydrate sources and sinks is altered, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…lesions damage vascular tissues in seagrass blades, disrupting the flow of carbohydrates within seagrass blades and resulting in accumulations of phenolics wherever carbohydrates are in overabundance, as predicted by Jones & Hartley (1999). Such responses are known from terrestrial plants, including birch, pine and poplar, and are predicted by the sink/source model of plant defense (Haukioja 1990, Tuomi et al 1991, Honkanen et al 1999, Arnold et al 2004). This model predicts that 'induced' responses arise when the allocation of carbon resources among tissues acting as carbohydrate sources and sinks is altered, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, herbivory on sorghum induced expression of nitrate and nitrite reductases that are required for nitrogen assimilation into Gln and Glu (Zhu-Salzman et al, 2004); expression of Glu synthase (also known as Gln oxoglutarate aminotransferase, or GOGAT) was induced by aphid feeding on N. attenuata (Voelckel et al, 2004); and aphid feeding induced Gln synthetase, which acts together with GOGAT in the Gln synthetase/GOGAT cycle, in celery (Apium graveolens; Divol et al, 2005). However, examination of multiple such data sets shows that either production or degradation amino acids can be preferred, depending on the specific plant-herbivore system being investigated and the type of tissue (local or systemic) being analyzed (Dorschner et al, 1987;Sandström et al, 2000;Arnold et al, 2004;Koyama et al, 2004;Caldana et al, 2011;Appel et al, 2012).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…In methyl jasmonate-treated or wounded Arabidopsis, radioactively labeled carbohydrates were imported into sink leaves within hours after treatment, and were incorporated into defense-related compounds such as cinnamic acid and phenolic glycosides (Ferrieri et al, 2012). When carbohydrate import was disrupted by removing source leaves or cutting vascular connections, hybrid poplar (Populus deltoides 3 Populus nigra) defenses were induced less efficiently (Arnold and Schultz, 2002;Arnold et al, 2004). In contrast to carbohydrate transport, labeled nitrogen tracking studies have shown little evidence of jasmonic acid-induced nitrogen transport to elicited leaves in poplar (Arnold et al, 2004;Appel et al, 2012).…”
Section: Reallocation Of Primary Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Black squares -7 days after the inoculation; gray circles -14 days after the inoculation. The lines represent linear adjustment at a probability level P<0.05 (Arnold et al 2004) playing a key role in defense mechanisms during pathogenesis (Rusjan et al 2012;Hura et al 2014a, b). The results of some recent studies provided evidence that the high level of phenolic compounds can be linked with low susceptibility of plants to fungal infection (Mikulic-Petkovsek et al 2014a, b).…”
Section: Discussionmentioning
confidence: 99%